Pancasila sebagai paradigma pembangunan industri 4.0 - Hanum, Fathikah Fauziah (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2019)
This article aims to find out the concept of Pancasila in the industrial revolution 4.0 byexamining Pancasila as a development paradigm. The development includes economic,education and science and technology development. The Industrial Revolution is tobecome a vision in various lives, especially focusing on economic growth. Thegovernment is focused on improving the economy, education is also designed to be ableto make human resources that can be competitive in the industrial sector. The problem isthat the orientation of development which is more focused on facing industrialdevelopment causes the goal of forming the national personality to be reduced. This wasfollowed by a weakening of national character. The development will not be great if it is notbased on values manifested in the morality of the nation, so that reorientation ofdevelopment is needed which refers to the Pancasila State philosophy, because Pancasilais basically a paradigm in development. The role of Pancasila is to provide some ethicalprinciples to economic development, education and science, and technology.